HUBUNGAN ANTARA KESEPIAN (LONELINESS) DENGAN SELF DISCLOSURE PADA MAHASISWA UNIVERSITAS TEKNOLOGI SUMBAWA YANG MENGGUNAKAN SOSIAL MEDIA (INSTAGRAM) - Khalifah Akbar, Syahdan; Suci Prapita Sari Abdullah, Elis (Jurnal TAMBORA, 2021)
Loneliness is an emotional and cognitive reaction in which individuals feel dissatisfied withsocial life due to unfulfilled expectations and few relationshipssocial he has. The purpose of this study was to determine the relationship betweenloneliness (loneliness) with self-disclosure to University of Technology studentsSumbawa who use social media (Instagram).This study uses a quantitative approach. Sampling technique inThis research uses purposive sampling technique. The sample in this studytotaling 97 students of the Sumbawa University of Technology. Research dataobtained by using research instruments in the form of two scales, namely theloneliness and self-disclosure scale.The results showed that there was a relationship between loneliness (loneliness)with self-disclosure with a correlation coefficient of 0.689 in the high category orstrong, and the value of Sig. (p count) = 0.000 or p <0.05, which means that there is a variable relationshipsignificant loneliness and self-disclosure. Positive value indicatesthat there is a unidirectional correlation, which means the higher the perceived lonelinessthe higher the self-disclosure made on social media.